Wangechi Mutu Storm King Art Center - Wangechi Mutu 1972- (Storm King Art Center, 2022)
Accompanying a 2022 exhibition at Storm King Art Center, New York, comprising large-scale bronzes, earthworks, and films by Wangechi Mutu, this publication includes a foreword by John P. Stern, President of Storm King, an essay situating Mutu's sculptures within an art historical context by Storm King's Artistic Director and Chief Curator, Nora Lawrence, an artist's statement by Mutu, and an essay by contributing author, Aisha Tandiwe Bell. Installation photography of Mutu's works sited in Storm King's expansive landscape, and inside the Art Center's Museum Building, illustrate the publication. The book is designed by Omnivore in collaboration with the Wangechi Mutu Studio.00Exhibition: Storm King Art Center, New York, USA (21.05-07.11.2022)
Wangechi Mutu exhibition. - Genaue Ausstellungsdaten ermittelt: May 21-November 7, 2022
Keywords: Wangechi Mutu -- 1972-; Bronzeplastik; Ausstellungskatalog -- Storm King Art Center -- 21.05.2022-07.11.2022 -- Mountainville, NY; Bildband